HUBUNGAN PESAN DAN MEDIA TERHADAP PENGETAHUAN PELANGGAN (STUDI KASUS PADA SOSIALISASI PENCEGAHAN PENYALAHGUNAAN LISTRIK DI AREA NAGOYA KOTA BATAM) - Ratnasari, Eeng; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2019)
PT bright PLN Batam is the largest electricity provider in Batam, which is actively conducting socialization regarding the correct use of electricity and a ban on electricity abuse. This socialization, although it has been carried out, still records high misuse rates, especially in the Nagoya service area. This study aims to examine the determinant factors of communication in the socialization of the knowledge of its customers. This research was conducted with descriptive quantitative method, where cluster sampling technique is used with a sample of 150 people. The level of research confidence is 95% or the error tolerance level is 5%, so that from 150 people obtained 105 samples. Data was collected by questionnaire instrument. The data that has been obtained is tested with the Pearson product moment correlation technique. From the results of this study it is known that all messages and media have a positive and significant relationship to customer knowledge in the socialization activities of prevention of electricity misuse conducted by PT bright PLN Batam in the Nagoya service area. It is recommended for PT bright PLN Batam to make the socialization message as easy to remember and related to the customer's daily life, as well as using the media according to customer preferences.